A national sports institute as a learning culture - Lee, J.; Price, N. (Physical Education and Sport Pedagogy, 2016)
Background and purpose: The aim of this study was to describe the learning culture for elite athletes who resided at the Australian Institute of Sport (AIS) from the perspective of the athletes themselves. As a government entity, the AIS is highly regulated by policies and strategies concerning allocation of funding, facilities, services, and resources. There is a substantial body of research examining government interest in elite sport and, in particular, national and state sporting institutes. These meso-level interactions within the AIS context no doubt have an impact on athlete learning. Learning in this context is political and economic as well as social. Thus, the cultural theory of learning is an important tool in considering the political agenda as an integral part of the learning process within the context of the AIS.